(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى التعرف على واقع تطبيق سياسات التسويق الداخلي في المصارف السورية من خلال إجراء دراسة مقارنة بين المصارف العامة والخاصة في مدى تطبيق هذه السياسات ( ثقافة الخدمة, التدريب الداخلي, نشر المعلومات التسويقية ), شملت الدراسة ثلاثة مصارف عامة (المصرف التجاري السوري, المصرف العقاري السوري, المصرف الزراعي), وثلاثة مصارف خاصة (البنك الدولي للتجارة والتمويل, البنك العربي, بنك عودة), ولتحقيق أهداف الدراسة تم بناء استبانة, وتطبيقها على عينة من العاملين والزبائن لدى المصارف الستة, بينت النتائج أن المصارف الخاصة تميل إلى تطبيق سياسات التسويق الداخلي بشكل أكبر وأوضح من المصارف العامة, ووجود اختلاف في تطبيق متغير ثقافة الخدمة باختلاف نوع المصرف (عام–خاص), ولا يوجد اختلاف في تطبيق متغير التدريب الداخلي باختلاف نوع المصرف(عام–خاص), ووجد اختلاف في تطبيق متغير نشر المعلومات التسويقية باختلاف نوع المصرف (عام–خاص) وإن المصارف الخاصة تطبق سياسات التسويق الداخلي بشكل أفضل من المصارف العامة. This research aims to recognize the reality of the application of internal marketing policies in the Syrian banking through a comparative study between public and private banks in the extent of the application of these policies (the culture of service, internships, Publishing of marketing information), the study included three public banks (Commercial Bank of Syria, real Estate Bank of Syria, the agricultural Bank), three private banks (international Bank for trade and finance, Arab Bank, Bank Audi), and to achieve the study objectives were to build a questionnaire, applied to a sample of employees and customers at the six banks, and the search is over to the following conclusions Private banks tend to apply the internal marketing policies are larger and clearer than the public banks, There is a difference in the application of the service culture variable depending on the type of bank (in-particular), There is no difference in the application of in-house training variable depending on the type of bank (in-particular), There is a difference in the application deployment marketing information variable depending on the type of bank (in-particular) and The private banks internal marketing policies applied better than public banks.